Handbook of export assistant in Norilsk Nickel Harjavalta Oy - Linja, Nina (Satakunnan ammattikorkeakoulu, 2018)
The purpose of this thesis was to investigate Norilsk Nickel Harjavalta Oy orientation process for export assistant’s position. Original thought was to create a handbook for future summer trainees and for their orientation process. The idea came up when I was working as a summer trainee in Norilsk Nickel Harjavalta Oy. Company did not have any specific problem regarding to the orientation, we just came up with the idea how the process could be improved. My task was to come up with the upgraded idea to their orientation process. Then the handbook idea was released and research started. This topic was chosen because there is always something that could be done better in orientation. The topic was current for the author because she had recently had her own orientation for the tasks of export assistant. Theoretical data for this thesis is gathered mainly from books, but reliable online articles and YouTube-videos are also used. The thesis was project-based and qualitative approach was applied when completing the empirical part. In interview the method was semi-structured and was held in Nornickel Harjavalta office. Interviews consist of relevant topics regarding the handbook and exporting process. Empirical part was gathered by making interviews to export assistants who have been working several years in this position. They both have had their own orientation and trained summer applicants. Therefore, this was a perfect opportunity to investigate the orientation process. They both have several years of experience regarding exporting, so their knowledge was important when gathering information to the handbook. With this qualitative method, purpose was to research the improvement possibilities to the orientation process. These interviews also gave more perspective to the whole exporting process and gave idea what kind of matters are essential to take into consideration when gathering the handbook.